2021
DOI: 10.1111/jcpe.13421
|View full text |Cite
|
Sign up to set email alerts
|

Laser parameters in systematic reviews

Abstract: To the Editor, As a researcher of laser in Periodontology, I have some concerns about mistaken laser concepts used in papers selected for systematic reviews that I would like to discuss in the present letter. I understand that science must be extensively debated, mainly in the field of new therapies as laser. Laser devices have been improving each year, and their effects are better understood in the last 10 years.A systematic review and meta-analysis, about non-surgical periodontal treatment with lasers, was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In general, high heterogeneity in methodologies such as plaque control methods, oral hygiene instructions provided to patients, technique and frequency of SRP sessions, laser parameters, output energy per surface unit (J/cm 2 ), frequency of aPDT sessions, and type of photosensitizer in RCTs also cause bias and prevent achieving reliable results. Moreover, a recent study [ 60 ] has identified that certain wavelengths should be used with blue photosensitizers, and there is no photodynamic reaction at wavelengths above 800 nm (infrared) with the blue type of PS (toluidine blue and methylene blue). Hence, blue photosensitizers are used just with 635-660 nm wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…In general, high heterogeneity in methodologies such as plaque control methods, oral hygiene instructions provided to patients, technique and frequency of SRP sessions, laser parameters, output energy per surface unit (J/cm 2 ), frequency of aPDT sessions, and type of photosensitizer in RCTs also cause bias and prevent achieving reliable results. Moreover, a recent study [ 60 ] has identified that certain wavelengths should be used with blue photosensitizers, and there is no photodynamic reaction at wavelengths above 800 nm (infrared) with the blue type of PS (toluidine blue and methylene blue). Hence, blue photosensitizers are used just with 635-660 nm wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding specific technologies used as adjunctive periodontal therapies have recently been raised in the context of aPDT. Following publication of the systematic review and meta‐analysis on the use of aPDT in non‐surgical periodontal treatment (Salvi et al, 2020), a subsequent letter to the editor raised concerns about some of the included studies, specifically that they utilized laser wavelengths that did not correspond to the absorption peak of the photosensitizer employed in the study (Damante, 2021). Given that, in order for a photodynamic reaction to occur, the absorption peak of the photosensitizer should be in the same range as the laser wavelength, the author makes the observation that in studies where this was not the case, then the desired photodynamic reaction would be unlikely to occur, and thus there would be little or no clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Reply to letter to the editor: "Laser parameters in systematic reviews" I appreciate the opportunity Dr. Damante's "letter to the editor" (Damante, 2021) and the JCPE's editorial office (on behalf of Profs.…”
mentioning
confidence: 99%
“…As correctly pointed out in that letter, the photodynamic reaction is dependent of the selection of the laser wavelengths according the absorption peak of each type of photosensitizer / dye (Damante, 2021). According to Dr. Damante and similarly to Salvi et al (2020), review, the AAP BEC review also included papers with unusual combinations of laser and dye (that is, aPDT approaches not in whole accordance to the "Principle of Photochemical Activation").…”
mentioning
confidence: 99%